IMPLEMENTATION OF AFFECTIVE ASPECT ASSESSMENT IN NEW BLOOM'S TAXONOMY IN THE TEACHING OF THE INDONESIAN NATIONAL ANTHEM "INDON ESIA RAYA" AT SMP N 2 BULAKAMBA - Bangkit Wijaya, Barkah (Jurnal Penelitian Musik, 2022)
In line with the development of education science, Bloom’s theory is transformed intro a cognitive aspect: dimensions of cognitive process and dimensions of knoeladge. Affective aspect revision becomes; recertion, gving response, giving value, organizing, and characterization, while the revision on the pyshomotor aspect become; imitating, applying, stabizing, constructing, and naturalizing. In this regard, the researching intends to further analyze its implementation, especially in the affective aspect of learning the art of music, especially the song “Indonesia Raya” at SMP N 2 Bulakamba. The research model used in this reseach is descriptive qualitative with a case approach. The basic approach is carried out in a multidisciplinary manner, namely using learning and learning theory that speciafically axamines the assessment of learning outcomes (New Taxonomy Bloom), as well as music theory. Data collection techniques in research use: observation, interviews, document study, and literature study. As for testing the validity of the data using source triangulation, including: (reduced), analyze, verity, and the presentation stage. The results of the study show that the assessment of affective aspect has imlications for the value of student character education such as love for the motherland, national spirit, and patriotsm. On the affective aspects of New Taxonomy Bloom, they include; Acceptance (understand, accept, and pay attention to the educational value of the character of love for the motherland, national spirit, and an attitude of patriotism, Providing a response (understanding the importance or educational values for the character of love for the motherland, national spirit, patriotism, and being happy to apply them; Giving value or aword (students understand the difference between the character education value of love for the motherland, national spirit, and patriotism; Organizing (understanding theoreticall and practically the development of other character education values from love of the motherland, national spirit, and patriotism; Characterization, (able to apply the character education values of love for the motherland, national spirit, and patriotism in everyday life, so that it become habituation and identity).